Uveal melanoma: From diagnosis to treatment and the science in between. Issue 15 (15th March 2016) - Chattopadhyay, Chandrani; Kim, Dae Won; Gombos, Dan S.; Oba, Junna; Qin, Yong; Williams, Michelle D.; Esmaeli, Bita; Grimm, Elizabeth A.; Wargo, Jennifer A.; Woodman, Scott E.; Patel, Sapna P.
Abstract : Melanomas of the choroid, ciliary body, and iris of the eye are collectively known as uveal melanomas. These cancers represent 5% of all melanoma diagnoses in the United States, and their age‐adjusted risk is 5 per 1 million population. These less frequent melanomas are dissimilar to their more common cutaneous melanoma relative, with differing risk factors, primary treatment, anatomic spread, molecular changes, and responses to systemic therapy. Once uveal melanoma becomes metastatic, therapy options are limited and are often extrapolated from cutaneous melanoma therapies despite the routine exclusion of patients with uveal melanoma from clinical trials. Clinical trials directed at uveal melanoma have been completed or are in progress, and data from these well designed investigations will help guide future directions in this orphan disease. Cancer 2016;122:2299–2312 . © 2016 American Cancer Society . Abstract : Patients with uveal melanoma often imprecisely receive the same treatment as patients with cutaneous melanoma. Because uveal melanoma is a unique subset of melanoma, its biology, immunology, and natural history demand closer investigation.